Interprofessional Inconsistencies in the Diagnosis of Shoulder Instability: Survey Results of Physicians and Rehabilitation Providers - Constantine P Nicolozakes; Xinning Li; Tim L Uhl; Guido Marra; Nitin B Jain; Eric J Perreault; Amee L Seitz (International Journal of Sports Physical Therapy)
# Background Clinicians of many specialties within sports medicine care for athletes with shoulder instability, but successful outcomes are inconsistent. Consistency across specialties in the diagnosis of shoulder instability is critical for care of the athlete, yet the extent of divergence in its diagnosis is unknown.